Bleeding Symptoms in Carriers of Hemophilia A and B - Mauser Bunschoten, E P; Houwelingen, J C van; Sjamsoedin Visser, E J M; Dijken, P J van; Kok, A J; Sixma, J J (Thrombosis and Haemostasis, 1988)
In order to investigate the bleeding tendency in clinically identified carriers of hemophilia, a self-administered questionnaire was held among 135 carriers of hemophilia A and B, 25 females with relatives with hemophilia and a matched group consisting of 60 females without relatives with hemophilia. Carriers of hemophilia appeared to suffer more often from bleeding than their relatives or the matched unrelated control group. A relation was seen between factor VIII :C or IX :C activity and the tendency to bleed. Obligatory carriers with normal factor VIII :C levels showed no bleeding tendency and were in this respect similar to a group of 25 females with relatives with hemophilia. This study shows that it is important to assay factor VIII: C or IX: C also in those women in whom the carrier status has already been established otherwise.
Keywords: Hemophilia; Carrier; Bleeding symptoms